The roles of extracellular vesicles in mental disorders: information carriers, biomarkers, therapeutic agents - Wang, Longkun; Liu, Ruixue; Wang, Ying (Frontiers in Pharmacology, 2025)
Mental disorders are complex conditions that encompass various symptoms and types, affecting approximately 1 in 8 people globally. They place a significant burden on both families and society as a whole. So far, the etiology of mental disorders remains poorly understood, making diagnosis and treatment particularly challenging. Extracellular vesicles (EVs) are nanoscale particles produced by cells and released into the extracellular space. They contain bioactive molecules including nucleotides, proteins, lipids, and metabolites, which can mediate intercellular communication and are involved in various physiological and pathological processes. Recent studies have shown that EVs are closely linked to mental disorders like schizophrenia, major depressive disorder, and bipolar disorder, playing a key role in their development, diagnosis, prognosis, and treatment. Therefore, based on recent research findings, this paper aims to describe the roles of EVs in mental disorders and summarize their potential applications in diagnosis and treatment, providing new ideas for the future clinical transformation and application of EVs.